Case Report: Imaging Features of Gallbladder Sessile Polyp Confirmed by Contrast-Enhanced Ultrasonography and Dynamic Computed Tomography in a Dog With Asymptomatic Chronic Cholecystitis - Lee, Jeongmin; Kang, Jinsu; Heo, Suyoung; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2022)
A 6-year-old dog was presented for health screening. It never suffered from any disease. Ultrasonography confirmed mass-like thickening with irregular margins protruding toward the gallbladder (GB) lumen. On contrast-enhanced ultrasonography (CEUS) and dynamic computed tomography (CT), contrast enhancement of the corresponding structures was confirmed in arterial phase. After cholecystectomy, cauliflower-like sessile polyps were identified. Histopathological examination revealed chronic lymphoplasmacytic cholecystitis. Bile culture revealed Escherichia coli growth. Our novel findings suggest that chronic cholecystitis should be considered as a differential diagnosis if contrast-enhanced sessile polyps of the GB are found on CEUS and dynamic CT.